2014
DOI: 10.1155/2014/915652
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Middle School Students’ Interest in Participating in an Incentive-Based Tobacco Prevention and Cessation Program in Connecticut

Abstract: Behavioral incentives have been used to encourage smoking cessation in older adolescents, but the acceptability of incentives to promote a smoke-free lifestyle in younger adolescents is unknown. To inform the development of novel, effective, school-based interventions for youth, we assessed middle school students' interest in participating in an incentive-based tobacco abstinence program. We surveyed 988 students (grades 6–8) attending three Connecticut middle schools to determine whether interest in program p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…One interpretation of our findings is that adolescents who are more responsive to rewards as indicated by high BAS may respond better to incentive-based (including monetary) smoking cessation interventions. High BAS is also associated with impulsivity, and in an earlier study, adolescents who reported higher impulsivity were more likely to report interest in incentive-based smoking cessation programs (Morean et al, 2014), and responded better when treatment included a behavioral incentive for abstinence (Morean et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…One interpretation of our findings is that adolescents who are more responsive to rewards as indicated by high BAS may respond better to incentive-based (including monetary) smoking cessation interventions. High BAS is also associated with impulsivity, and in an earlier study, adolescents who reported higher impulsivity were more likely to report interest in incentive-based smoking cessation programs (Morean et al, 2014), and responded better when treatment included a behavioral incentive for abstinence (Morean et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The materials represented six topics: (a) increasing awareness of high-risk situations, (b) addressing withdrawal syndrome, (c) negotiating cessation barriers, (d) encouraging oneself through reinforcing one's resolve to make the right decision, (e) addressing negative responses associated with hunger, anger, loneliness, and fatigue, and (f) evaluating the strength of various stressors. These course topics were derived from previous smoking-cessation programs [15,17,18]. To advance students' engagement, an educational game was designed for each topic (Table 1).…”
Section: Design Of the Digital Educational Gamesmentioning
confidence: 99%
“…Accordingly, it is important that assessments of impulsivity are tested for measurement invariance across racial groups. Morean et al (2014) found that the two-dimensional structure of the BIS-Brief was invariant across race (White vs. non-White) in a sample of adults that was 70% White. No studies that we are aware of have specifically tested whether the BIS-Brief is invariant across race in adolescents.…”
mentioning
confidence: 93%
“…These results are consistent with research supporting the multidimensionality of impulsivity (Cyders & Coskunpinar, 2011; de Wit, 2009; Dougherty et al, 2005; Reynolds et al, 2008) and the distinct contributions of both self-regulation ability and behavioral impulsivity to engagement in problem behaviors (e.g., Eisenberg et al, 2005; Eisenberg et al, 2009; Schreiber, Grant, & Odlaug, 2012). Additionally, the two-dimensional model has demonstrated adequate fit and internal consistency when applied to community samples of middle school (Morean, Camenga, et al, 2014) and high school students (Bold et al, 2017), as well as adolescent cigarette smokers (Morean et al, 2015). It is possible that the underwhelming model fit indices for the unidimensional BIS-Brief reflect the fact that the two-dimensional structure better represents the construct being assessed.…”
mentioning
confidence: 99%